BUDDYRESC - Uchà´a, Iãh; Pinheiro, Gabriel Pereira; Furtado , Guilherme H. P. N.; Vasconcelos, Gustavo Henrique; Menezes, João Vitor de Pina; Siqueira, Lucas Evangelista; Moreira, Ronivaldo Silva; Santos Junior, William Pereira (CIPEEX, 2022)
ACCORDING TO RESEARCHES CONDUCTED ON 2015, MORE THAN 170 THOUSAND ANIMALS ARE UNDER CARE OF AROUND 370 NON-GOVERNMENTAL ORGANIZATIONS (NGOS) WAITING FOR ADOPTION ON BRAZIL, IN ADDITION TO MORE THAN 30 MILLION STRAY CATS AND DOGS. MAKING PET NEGLECT AND ABANDONMENT SOMETHING NOT JUST CRUEL, BUT ALSO A PROBLEM OF SANITARY NATURE. TO FACE THIS ISSUE ON A LOCAL SCOPE, BUDDYRESC IS BORN AS A MOBILE APP WITH THE PURPOSE OF FACILITATING PET ADOPTION AND REDUCING THE OCCURRENCE OF ANIMAL ABANDONMENT, MAKING THIS PROCESS EASIER, USER FRIENDLY AND MORE HUMANIZED. THE PROJECT AIMS TO ALLOW VERIFIED PEOPLE AND ORGANIZATIONS TO REGISTER ANIMALS AND CAMPAIGNS SO USERS CAN VIEW THEM, CONTACT CURRENT TUTORS AND GIVE A NEW HOME FOR THOSE IN NEED. THIS WAY, IF SOMEONE IS FOSTERING OR TUTORING AND COULD NOT TAKE CARE OF A PET ANYMORE, THEY WOULD REGISTER THE ANIMAL ON THE SYSTEM INSTEAD OF IMMEDIATELY ABANDONING IT, GIVING THEM ANOTHER CHANCE OF STAYING OF THE STREETS.